Cocreating evidence‐informed health equity policy with community. (3rd March 2022) - Walker, Sarah Cusworth; White, Johnna; Rodriguez, Victor; Turk, Emily; Gubner, Noah; Ngo, Sally; Bekemeier, Betty
Abstract: Objective: To explore the feasibility of a rapid, community‐engaged strategy to prioritize health equity policy options as informed by research evidence, community‐voiced needs, and public health priorities. Data Sources: Data came from residents in a midsized, demographically, and geographically diverse county over a period of 8 months in 2020 and an evidence review of the health equity policy literature during the same time period. Study Design: A descriptive case study is used to explore the feasibility and potential value of a community codesigned approach to establish community priorities for health equity policy. Data Collection/Extraction Methods: Evidence synthesis of health equity policy was conducted parallel to 15 community listening sessions across the county to elicit information on health needs. We used scoping review methods to obtain literature from academic databases and scholarly public health and policy organizations. This information was cross walked with themes from the listening sessions to identify 10 priority policy areas, which were taken back to the community for 15 participatory discussion and ranking sessions. Principal Findings: The process appeared to authentically engage the input of 200 community members representative of minoritized groups while identifying 99 evidence‐informed policy levers to promote health equity. Discussion and ranking activities were successful in facilitating community discussion and policy decision making. Remote platforms may have limited the engagement of some residents while promoting the participation of others. Conducting information integration within the research team prior to community policy ranking sessions limited the community ownership over how policies were interpreted and communicated. Conclusions: A combination of information integration and community ranking activities can be used to achieve community‐engaged policy prioritization of options in a fairly rapid period of time. While this process provides an example of authentic community ownership of policy prioritization, the compressed timeline limited the community's engagement in the information integration phase.